Florida Scorpionfly, Panorpa floridana Byers (Insecta: Mecoptera: Panorpidae) - Louis A. Somma; James C. Dunford (EDIS)
Have you seen this insect? No living individuals of Panorpa floridana have ever been observed. Knowledge of this species of scorpionfly is limited to five specimens from Alachua and Clay counties in northern peninsular Florida, the last one collected in 1982. This 4-page fact sheet was written by Louis A. Somma and James C. Dunford, and published by the UF Department of Entomology and Nematology, September 2012.